2022
DOI: 10.1038/s41421-022-00450-x
|View full text |Cite
|
Sign up to set email alerts
|

RNA G-quadruplex formed in SARS-CoV-2 used for COVID-19 treatment in animal models

Abstract: The ongoing COVID-19 pandemic has continued to affect millions of lives worldwide, leading to the urgent need for novel therapeutic strategies. G-quadruplexes (G4s) have been demonstrated to regulate life cycle of multiple viruses. Here, we identify several highly conservative and stable G4s in SARS-CoV-2 and clarify their dual-function of inhibition of the viral replication and translation processes. Furthermore, the cationic porphyrin compound 5,10,15,20-tetrakis-(N-methyl-4-pyridyl)porphine (TMPyP4) targeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 44 publications
7
46
4
Order By: Relevance
“…More recently, TMPyP4 G4-ligands, already known for its antiviral activities against HIV-1, also exhibited antiviral activity against SARS-CoV-2. Remarkably, in Syrian hamster and transgenic mouse models of SARS-CoV-2 infection, administration of TMPyP4 resulted in a significant reduction in viral loads and lung injury ( Qin et al, 2022 ). In the same study, the activity of TMPyP4 proved to be significantly stronger than that of remdesivir.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, TMPyP4 G4-ligands, already known for its antiviral activities against HIV-1, also exhibited antiviral activity against SARS-CoV-2. Remarkably, in Syrian hamster and transgenic mouse models of SARS-CoV-2 infection, administration of TMPyP4 resulted in a significant reduction in viral loads and lung injury ( Qin et al, 2022 ). In the same study, the activity of TMPyP4 proved to be significantly stronger than that of remdesivir.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this drug may represent a safe alternative to remdesivir and dexamethasone with both antiviral and anti-inflammatory properties [ 97 ]. Interestingly, G-quadruplexes specific ligands, namely 5,10,15,20-tetrakis-( N -methyl-4-pyridyl)porphine (TMPyP4), showed better antiviral effects than remdesivir on the Vero E6 cells, Syrian hamster and human angiotensin-converting enzyme 2 (hACE2) transgenic mouse model of SARS-CoV-2 infection, with no significant toxicity [ 98 ]. Most importantly, this study provided an alternative strategy for COVID-19 treatment by targeting the secondary genomic structures of SARS-CoV-2, paving the way to the rational design and synthesis of new safer agents.…”
Section: Recent Studies For New Drugsmentioning
confidence: 99%
“…Through an intensive investigation they found that targeting SARS‐CoV‐2 G4s by PDP and TMPyP4 can significantly inhibit SARS‐CoV‐2 infection in cell‐based assays. [ 52 ] And TMPyP4 showed more potent anti‐SARS‐CoV‐2 activity than PDP and can significantly ameliorate lung damage caused by SARS‐CoV‐2 infection in animal models. [ 52 ] These findings reveal the biological roles of viral RNA G4s in SARS‐CoV‐2 life cycle and highlight the potential of viral RNA G4s as a druggable target for COVID‐19 prevention and treatment.…”
Section: Identification Of G4s In Sars‐cov ‐2 Genomementioning
confidence: 99%
“…On the other hand, due to the availability of a negative control compound TMPyP2, TMPyP4 is widely employed as a tool for studying G4s. [ 7 , 52 , 70 ] TMPyP2 cannot stack on the G4 because of the steric‐hindrance effect, leading to no biological effects. [ 70 ] In viruses, TMPyP4 was also employed to investigate the roles of G4s in the life cycle of various viruses, such as HIV, [ 71 ] Hepatitis C virus (HCV), [ 37 ] Zika virus (ZIKV) [ 38 ] and Ebola virus (EBOV).…”
Section: G4 Ligands Against Sars‐cov ‐2mentioning
confidence: 99%
See 1 more Smart Citation